An Analysis Of Steam Powered Electric Power Plant Utilizing Bagsage In A Factory - Oki Ardhian Fibianto; Adi Sastra P Tarian; Muhammad Fahreza (Sean Institute, 2024)
As the years increase, the population increases and fossil fuel reserves decrease, there is an urgent need for alternative energy sources that are environmentally friendly, efficient and effective. One promising alternative is to use sugarcane bagasse as biomass fuel for electricity generation. As a sugar cane producing country, Indonesia has great potential in utilizing sugar cane milling waste as a renewable energy source. This research aims to assess the potential of sugarcane bagasse as a fuel for electricity generation and determine the capacity of electrical energy that can be produced from this fuel. In the context of steam power plants, fuel selection is a crucial aspect because it is directly related to the efficiency and performance of the plant. Apart from conventional options such as diesel and coal, bagasse offers an attractive alternative. From the test results, it is known that bagasse has a calorific value of 2370.5 kcal/kg. Analysis shows that good quality fuel can produce up to 2.8 MW of electrical power. These findings confirm that sugarcane bagasse has great potential as fuel for electricity generation that is economical and easy to obtain.